The Intracellular Cholesterol Transport Inhibitor U18666A Inhibits the Exosome-Dependent Release of Mature Hepatitis C Virus - Elgner, Fabian (J Virol, 2016)
Hepatitis C virus (HCV) particles are described as lipoviroparticles which are released similarly to very-low-density lipoproteins (VLDLs). However, the release mechanism is still poorly understood; the canonical endoplasmic reticulum-Golgi intermediate compartment (ERGIC) pathway as well as endosome-dependent release has been proposed. Recently, the role of exosomes in the transmission of HCV has been reported. Only a minor fraction of the de novo-synthesized lipoviroparticles is released by the infected cell. To investigate the relevance of multivesicular bodies (MVBs) for viral morphogenesis and release, the MVB inhibitor U18666A was used. Intracellular trafficking was analyzed by confocal microscopy and electron microscopy. Moreover, an mCherry-tagged HCV variant was used. Conditions were established that enable U18666A-dependent inhibition of MVBs without affecting viral replication. Under these conditions, significant inhibition of the HCV release was observed. The assembly of viral particles is not affected. In U18666A-treated cells, intact infectious viral particles accumulate in CD63-positive exosomal structures and large dysfunctional lysosomal structures (multilamellar bodies). These retained particles possess a lower density, reflecting a misloading with lipids. Our data indicate that at least a fraction of HCV particles leaves the cell via the endosomal pathway. Endosomes facilitate the sorting of HCV particles for release or degradation. IMPORTANCE There are still a variety of open questions regarding morphogenesis and release of hepatitis C virus. The HCV-infected cell produces significant more viral particles that are released, raising the question about the fate of the nonreleased particles. Moreover, the relevance of the endosomal pathway for the release of HCV is under debate. Use of the MVB (multivesicular body) inhibitor U18666A enabled a detailed analysis of the impact of MVBs for viral morphogenesis and release. It was revealed that infectious, fully assembled HCV particles are either MVB-dependently released or intracellularly degraded by the lysosome. Our data indicate that at least a fraction of HCV particles leaves the cell via the endosomal pathway independent from the constitutive secretory pathway. Our study describes a so-far-unprecedented cross talk between two pathways regulating on the one hand the release of infectious viral particles and on the other hand the intracellular degradation of nonreleased particles.